Vídeo sobre cuidados paliativos para idosos: ferramenta educativa para capacitação de profissionais de saúde - Meireles, Danielle Silva de (2021)
Introduction: The ascension of techology linked to health has been engendering a crescent advance on search for heal and treatment of many chronic diseases today unhealing. Life expectancy is directly impacted because elderly population tend to live more. Progressive populational aging connected to exponential increase of cancer cases and chronic degenerative diseases with slow evolution generates larger committal and functional dependence for elderly population. Palliative Cares insert in this scenery as an extremely important speciality to professional practice aiming life quality, prevention and relief for suffering of patients and their relatives during this phase of life finitude. Aims: from empirical indicators approached by literature, to create a video for methodological support on professional capacity courses about palliative care for elderly and to validate this tool towards health professionals who act on palliative cares. Method: the first step of methodological study brings an integrative literature review, extracting empirical material from 5 data bases between August and October 2020: BVS, BDENF, Lilacs, Web of Science e Scopus. This first stage still includes researches, experience reports, case studies and scientific articles with primary data over the last 5 years, with all the text available; repetitive articles, scientific works presented in congresses or do not concerrned to te search question were excluded. According to such criteria, 27 articles composed the final sample. The second stage, for its turn, creates a screenplay with 6 scenes for the video, whose character’s speech were elaborated from results of the integrative review. Subsequently, this script was validated by specialist professionals according to the Content Validation Index (CVI). Results: Professionals’ knowledge is still very limitated. Despite recognizing the need, they do not know when nor how to approach elderly and their relatives about the terminality of life. Ineffective communication and defcit on professional formation were contrasted as the biggest challenges for the palliative assistance, justifying the importance of creating tools for better professional capacity aiming to modify this scenery. Scenes approached results of five thematic categories (concepts and purposes, communication, association with specialities, difficulties and challenges and directives preceded by will) and were validated by index higher than 91.66%, confirming pertinence of building the video. Conclusion: About Palliative Care, do not exist right or wrong conducts, because elderly and/or their family’s decision is always legitimate and must be respected. When preferences about death be discussed more naturally, discussions will no longer be taboo and it will become less frightening. Thencefoward will be easier to respect the will of the human being face to the finite process of his life.